Heat transfer phenomena of copper-graphene nanocomposite coated aluminium heat spreaders: An interferometric study. (25th July 2022) - Sainudeen, Shijina S.; Joseph, Antony; Joseph, Mathew; Sajith, V.
Graphical abstract: Highlights: Heat transfer study of Graphene nanocomposite coated Aluminium heat spreaders. Electrodeposition of Cu & Cu -Gr nanocomposite coating on Aluminium. Mach-Zehnder Interferometry for transient heat transfer studies. Higher lateral heat dissipation rate for Cu-Gr composite coated Al heat spreaders. Copper-Graphene nanocomposite coated Aluminium as an effective heat spreader for low discharge batteries. Abstract: The formation of thermal hot spots is one of the most significant challenges in operating battery packs of electric vehicles (EVs). Aluminium (Al) is a common material for heat spreaders; however, its capability to dissipate heat in the event of a hot spot formation is limited by its thermal conductivity. The present work focuses on addressing this issue by coating the Al heat spreader with copper-graphene (Cu-Gr) nanocomposite to improve its heat dissipation characteristics. DC electrodeposition technique was employed for coating Cu- Gr nanocomposite material on Al plate, with an optimized graphene concentration of 0.5 g/L in the electrolyte bath, which showed maximum graphene loading in the coating. The Mach-Zehnder interferometric technique was employed to analyze the heat dissipation characteristics of Al heat spreaders, which is a novelty here. The real-time variation of heat dissipation and Nusselt number were obtained using Naylor's method. A comparative heat dissipation study was conducted among plain Al substrate, Cu film deposited Al substrate, and Cu-Gr nanocomposite film deposited Al substrate for three capacity ratings (C-rates), namely; 0.5 C, 1 C, and 3 C assuming a 5 Wh rated battery. The temperature difference between the center and the top of the Al heat spreader plate was the minimum for the composite coated plate. The drop in the temperature difference for the modified heat spreader was 66%, 55%, and 41% for 0.5 C, 1 C, and 3 C, respectively, compared to the bare Al heat spreader. The higher Nuavg values obtained from interferometric calculations for Cu-Gr composite coated heat spreaders indicate the uniform heat distribution along the surface than the Al heat spreader. The Cu-Gr composite coated Al substrate is a promising heat spreader candidate for maintaining uniform temperature in battery packs, extending battery life.